1980
DOI: 10.1063/1.328142
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient plasma heating through superelastic laser energy conversion

Abstract: Superelastic laser energy conversion has been shown to be capable of extremely rapid rates of plasma heating with relatively modest values of laser irradiance. In the case of a boron III plasma, dTe /dt≳1013 °K sec−1 has been predicted for a initial boron III ion density of 1017 cm−3. The laser irradiance needed to achieve this rate of change of the free-electron temperature is about 5×108 W cm−2 per cm of path length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We assume that the electron concentration and temperature do not change significantly due to the laser excitation. As stated by Measures et al [19], the collisional transfer of energy from the excited atoms to plasma at a number density of about 10 12 cm −3 is negligible.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We assume that the electron concentration and temperature do not change significantly due to the laser excitation. As stated by Measures et al [19], the collisional transfer of energy from the excited atoms to plasma at a number density of about 10 12 cm −3 is negligible.…”
Section: Discussionmentioning
confidence: 80%
“…The upper limit of the concentration range where this method can be applied reaches about 10 14 cm −3 . For higher densities the results might be strongly affected by disturbing collisional processes (such as energy pooling collisions [14], mixing of population of excited atoms by electron impact [13] or heating of electrons by the laser pulse [19]), which were neglected in our approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical approach of laser ionization by resonant light for long laser pulses (hundreds of nanoseconds) was given by Measures et al [8] and Bobin and Zaibi [9]. While, the model of few nanoseconds exciting pulses is presented by Stacewicz and Topulos [10].…”
Section: −3mentioning
confidence: 99%
“…Under saturation conditions, Measures [17] and Measures et al [18] have shown that, the redistribution of the population between the two laser coupled states occurs in a time approximately given by:…”
Section: The Theoretical Modelmentioning
confidence: 99%